Identifying the Gaps Between Public Health Training and Practice: A Workforce Competencies Comparative Analysis - Osnat Bashkin; Robert Otok; Ori Kapra; Kasia Czabanowska; Paul Barach; Paul Barach; Orna Baron-Epel; Keren Dopelt; Keren Dopelt; Mariusz Duplaga; Lore Leighton; Hagai Levine; et al. (Frontiers Media S.A., 2022)
Objectives: The study aimed to generate insights on how best to enhance the compatibility between Public Health training program competencies and the implementation of competencies required by employers to address current and emerging public health needs.Methods: A survey adapted from the WHO-ASPHER Competency Framework for the Public Health Workforce was conducted online among Israeli public health managers from August to November 2021. The survey was formulated to mirror Essential Public Health Operations. Forty-nine managers participated (37.6% response rate) in an assessment of 44 public health competencies and the core organizational public health operations.Results: Analysis of Essential Public Health Operations revealed a notably high deficiency reported for Advocacy Communication and Social Mobilization for health competencies. Collaborations and Partnership and, Leadership and System Thinking were the most reported insufficient competencies, particularly in health departments and research institutes. Governmental offices reported Organizational Literacy and Adaptability competencies being deficient. Deficiencies were more impactful as the level of expertise increased.Conclusion: There is a clear need for public health professionals to acquire versatile and innovative competencies in response to the ever-changing health threats.